Redescription of Physalaemus barrioi (Anura: Leiuperidae) - Provete, Diogo B. [UNESP]; Garey, Michel V. [UNESP]; Toledo, Luis Felipe; Nascimento, Juliana; Lourenco, Luciana B.; Rossa-Feres, Denise de C.; Haddad, Celio Fernando Baptista [UNESP] (Amer Soc Ichthyologists & Herpetologists, 2012)
Physalaemus barrioi is a poorly known frog endemic to the highlands of Serra da Bocaina in the Atlantic Forest of southeastern Brazil. Herein, we redescribe the species based on the type series and new specimens collected at the type locality. We also present additional data on its vocalization, karyotype, and tadpole, including the external morphology, internal oral features, and chondrocranium. Physalaemus barrioi can be diagnosed by the following combination of characters: SVL in males larger than 24 mm; inguinal glands associated with dark ocelli; throat and vocal sac dark brown; and chest dark with small light blotches. Bioacoustical characteristics also distinguish P. barrioi from all other species of Physalaemus. The tadpole of P. barrioi is very similar to those of the P. gracilis group, from which it can be distinguished by several characteristics, including marginal papillae in a single row, absence of submarginal papillae, elliptical nares, and upper jaw sheath in a wide arch.